High-index-contrast grating enhanced laser - Yu, Jiahang (2014)
Lasers have been a hot topic for a long time, since it can be widely applied in various fields, such as consumer devices, medical treatment, industry field, and even military application. Different kinds of lasers are used for different applications. For example, the vertical-cavity surface-emitting lasers(VCSELS), which are also the objects studied in this project, are key devices for many applications in photonic industry, one of which is fiber optical communication.